Ionic liquid electrodeposition of strain-released Germanium nanowires as stable anodes for lithium ion batteries. Issue 24 (12th June 2017) - Hao, Jian; Yang, Yu; Zhao, Jiupeng; Liu, Xusong; Endres, Frank; Chi, Caixia; Wang, Binsheng; Liu, Xiaoxu; Li, Yao
Abstract : With the growing demand for portable and wearable electronic devices, it is imperative to develop high performance Li-ion batteries with long life times. Abstract : With the growing demand for portable and wearable electronic devices, it is imperative to develop high performance Li-ion batteries with long life times. Germanium-based materials have recently demonstrated excellent lithium-ion storage ability and are being considered as the most promising candidates for the anodes of lithium-ion batteries. Nevertheless, the practical implementation of Ge-based materials to Li-ion batteries is greatly hampered by the poor cycling ability that resulted from the huge volume variation during lithiation/delithiation processes. Herein, we develop a simple and efficient method for the preparation of Ge nanowires without catalyst nanoparticles and templates, using ionic liquid electrodeposition with subsequent annealing treatment. The Ge nanowire anode shows improved electrochemical performance compared with the Ge dense film anode. A capacity of ∼1200 mA h g −1 after 200 cycles at 0.1 C is obtained, with an initial coulombic efficiency of 81.3%. In addition, the Ge nanowire anode demonstrates superior rate capability with excellent capacity retention and stability (producing highly stable discharge capacities of about 620 mA h g −1 at 5 C). The improved electrochemical performance is the result of the enhanced electron migration and electron transport paths of the nanowires, and sufficient elasticity to buffer the volume expansion. This approach encompasses a low energy processing method where all the material is electrochemically active and binder free. The improved cycling stability and rate performance characteristics make these anodes highly attractive for the most demanding lithium-ion applications.